Pelatihan Pembuatan Soal Online untuk Guru Pendidikan Jasmani SD di Kecamatan Tanjung Karang Barat Kota Bandar Lampung - Surisman; Herman Tarigan; Sudirman Husin (Jurusan Ilmu Pendidikan - Universitas Lampung, 2022)
One of the impacts of the COVID-19 pandemic is the transformation of learning media that used to use more face-to-face systems in the classroom to now become online systems. With this policy, all teachers conduct distance learning. Because of this policy, problems arise because not all teachers are proficient in using internet technology to support online learning activities and need assistance and training first. One cool feature that is intended for the world of education is the quiz creation feature that can be set using Google Formulars. Community service aims to improve the insight and skills of teachers in using the Google Form application as an online distance learning medium. The method of implementing this activity is carried out using online media in the form of tutorials and discussions on how to make online media questions using the Google Form application. The activity results showed that the training participants had understood the principles of learning and were able to apply online-based learning using the google form application. In this community service activity can be concluded that 88% of the training participants can apply learning by utilizing google form media as a learning tool at school.